2022
DOI: 10.1007/s00330-022-08819-y
|View full text |Cite
|
Sign up to set email alerts
|

Forensic age assessment by 3.0 T MRI of the wrist: adaption of the Vieth classification

Abstract: Objectives In order to find a reliable method to correctly assess majority in both sexes by MRI, a study was conducted to evaluate the applicability of the recently presented Vieth classification in wrist MRI, after it had originally been proposed for knee MRI. Methods After receiving a positive vote by the ethics committee, the left-hand wrists of 347 male and 348 female volunteers of German nationality in the age bracket 12–24 years were scanned. Before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Then, since its first introduction in 2018, the classification system by Vieth et al [14] has repeatedly been shown to be suitable for determining majority in both sexes when applied to the DFE [14][15][16]. Furthermore, the applicability of this classification system has also been proven for other ossification centers, such as the proximal humeral epiphysis [31], the two wrist epiphyses (distal radius and ulna) [32], and the proximal tibial epiphysis [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Then, since its first introduction in 2018, the classification system by Vieth et al [14] has repeatedly been shown to be suitable for determining majority in both sexes when applied to the DFE [14][15][16]. Furthermore, the applicability of this classification system has also been proven for other ossification centers, such as the proximal humeral epiphysis [31], the two wrist epiphyses (distal radius and ulna) [32], and the proximal tibial epiphysis [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, the fusion between the distal ends of both bones and their shafts begins in females at the age of thirteen or fourteen years, and in males at the age of fifteen or sixteen years (Hassan et al, 2016;Ottow et al, 2022). The distal ends of both bones completely fuse with their shafts at the age of the seventeenth year in females and the eighteenth to the nineteenth year in males.…”
Section: Introductionmentioning
confidence: 99%